Efficient Learning for the Poor : Insights from the Frontier of Cognitive Neuroscience - Abadzi, Helen (Washington, DC : World Bank, 2012)
This book integrates research into applications that extend from preschool brain development to the memory of adult educators. In layman's terms, it provides explanations and answers to questions such as: Why do children have to read fast before they can understand what they read? How do health, nutrition, and stimulation influence brain development? Why should students learn basic skills in their maternal language? Is there such a thing as an untrained teacher? What signs in a classroom show whether students are getting a quality education? How must information be presented in class so that students can retain it and use it? What training techniques are most likely to help staff put their learning into use? This book is intended for use by policymakers, donor agency staff, teacher trainers, supervisors, and inspectors, as well as university professors and students.